1975
DOI: 10.1083/jcb.65.3.631
|View full text |Cite
|
Sign up to set email alerts
|

The fate and origin of the nuclear envelope during and after mitosis in Amoeba proteus. I. Synthesis and behavior of phospholipids of the nuclear envelope during the cell life cycle.

Abstract: The synthesis and behavior of Amoeba proteus nuclear envelope (NE) phospholipids were studied. Most NE phospholipid synthesis occurs during G~ and little during mitosis or S (A. proteus has no G1 phase). Autoradiographic observations after implantation of [~H]choline nuclei into unlabeled ceils reveal little turnover of NE phospholipid during interphase but during mitosis all the label is dispersed through the cytoplasm. Beginning at telophase all the NE phospholipid label returns to the daughter NEs. This obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Metabolic labeling of Chinese hamster ovary cells indicated that at least 50% of the nuclear envelope phospholipid present in G 2 was used to resynthesize the nuclear envelopes of the daughter cells (45). Studies with Amoeba proteus are worthy of mention because of their unique approach (46). Autoradiographic observations following implantation of [ 3 H]choline-labeled nuclei into unlabeled cells revealed little turnover of nuclear membrane phospholipid during interphase; however, during mitosis the label was dispersed throughout the cytoplasm coincident with the degradation of the nuclear envelope.…”
Section: G 2 and M Phasesmentioning
confidence: 99%
“…Metabolic labeling of Chinese hamster ovary cells indicated that at least 50% of the nuclear envelope phospholipid present in G 2 was used to resynthesize the nuclear envelopes of the daughter cells (45). Studies with Amoeba proteus are worthy of mention because of their unique approach (46). Autoradiographic observations following implantation of [ 3 H]choline-labeled nuclei into unlabeled cells revealed little turnover of nuclear membrane phospholipid during interphase; however, during mitosis the label was dispersed throughout the cytoplasm coincident with the degradation of the nuclear envelope.…”
Section: G 2 and M Phasesmentioning
confidence: 99%
“…However, in the case of Acanthamoeba, it was reported that trophozoites are formed in the mitotic phase of cell division cycle. Moreover, the absence of the G1 phase has been observed in some protists including Amoeba proteus [59]. However, an extended G1 phase can be observed under certain conditions.…”
Section: Cell Cyclementioning
confidence: 99%
“…The function of those portions of the sperm nuclear envelope that remain intact is unknown; their persistence during pronuclear development suggests that the sperm nuclear envelope is not homogenous and possesses features specific to the morphogenesis of the sperm nucleus into a male pronucleus. Factors and mechanisms regulating the disappearance of the sperm nuclear envelope have not been determined, and how this process is related to nuclear envelope disruption in mitotic cells is unclear (Johnson and Rao, 1971;Maruta and Goldstein, 1975;Masui and Markert, 1971;Masui and Clarke, 1979). It is noteworthy that breakdown of the sperm nuclear envelope occurs in proximity to the female pronucleus but the pronuclear envelope of the female pronucleus remains intact (Longo, 1973(Longo, ,1981.…”
Section: Morphogenesis Of Incorporatedmentioning
confidence: 99%